METRIC-EF: magnetic resonance enterography to predict disabling disease in newly diagnosed Crohn's disease—protocol for a multicentre, non-randomised, single-arm, prospective study. Issue 10 (3rd October 2022) - Kumar, Shankar; Plumb, Andrew; Mallett, Sue; Bhatnagar, Gauraang; Bloom, Stuart; Clarke, Caroline S; Hamlin, John; Hart, Ailsa L; Jacobs, Ilan; Travis, Simon; Vega, Roser; Halligan, Steve; et al.
Abstract : Introduction: Crohn's disease (CD) is characterised by discontinuous, relapsing enteric inflammation. Instituting advanced therapies at an early stage to suppress inflammation aims to prevent future complications such as stricturing or penetrating disease, and subsequent surgical resection. Therapeutics are effective but associated with certain side-effects and relatively expensive. There is therefore an urgent need for robust methods to predict which newly diagnosed patients will develop disabling disease, to identify patients who are most likely to benefit from early, advanced therapies. We aim to determine if magnetic resonance enterography (MRE) features at diagnosis improve prediction of disabling CD within 5 years of diagnosis. Methods and analysis: We describe the protocol for a multicentre, non-randomised, single-arm, prospective study of adult patients with newly diagnosed CD. We will use patients already recruited to the METRIC study and extend their clinical follow-up, as well as a separate group of newly diagnosed patients who were not part of the METRIC trial (MRE within 3 months of diagnosis), to ensure an adequate sample size. Follow-up will extend for at least 4 years. The primary outcome is to evaluate the comparative predictive ability of prognostic models incorporating MRE severity scores (Magnetic resonance Enterography Global Score (MEGS), simplified MAgnetic Resonance Index of Activity (sMaRIA) and Lémann Index) versus models using standard characteristics alone to predict disabling CD (modified Beaugerie definition) within 5 years of new diagnosis. Ethics and dissemination: This study protocol achieved National Health Service Research Ethics Committee (NHS REC), London—Hampstead Research Ethics Committee approval (IRAS 217422). Our findings will be disseminated via conference presentations and peer-reviewed publications. Trial registration number: ISRCTN76899103 .